OPTIMALISASI PENGGUNAAN LAHAN DI KABUPATEN LUMAJANG - Laili Ayu Maulida; Mochammad Munir (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
Land use in Lumajang Regency is dominated by agricultural land. However, over time there was a conversion of agricultural land into residential land as a result of an increase in population. The purpose of this study was to determine the pattern and area of optimal land-use allocation increase economic value in Lumajang Regency. The method used in this study was linear programming with the simplex method. The maximum farming income obtained from optimizing land use is Rp710,306,800,000.00. The optimal land-use area for paddy fields is 42,686.71 ha, the protected forest is 12,652 ha, and residential land is 18,284 ha. The optimal proportion of land use is 58% rice fields, 17% protected forests, and 25% settlements. The optimal paddy field area has decreased by 6,003.26 ha from the land area in 2018 because there are paddy fields that do not match their characteristics. The largest area of rice field reduction in Candipuro District is 2,138.51 ha. Meanwhile, the direction for the allocation of residential land has increased settlement land from 2018 with an area of 1,114.1 ha. The development of residential land is allocated to land that has been planned for settlement in the Spatial Planning (RTRW), potential land that has a slope value of 0 - 25%, and areas with low population density. The largest additional area of residential land in Pronojiwo District is 300 ha.